THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND DIET PROVISION IN DIABETES PATIENTS - Timba, Velenia Kahi; Gunawan, Yosephina Elizabeth Sumartini; Landi, Melkisedek; Mulu, Servasius To'o Jala (Nurse and Holistic Care, 2024)
Introduction: Effective diabetes management requires strict adherence to dietary guidelines. Family support plays a critical role in helping patients with diabetes maintain appropriate nutritional practices. Objective: This study aims to analyze the relationship between family support and the dietary management of diabetes patients. Methods: This research was conducted at a Community Health Center in East Sumba Regency using a cross-sectional method. The Independent Variable is Family Support with sub-variables of Assessment Support, Instrumental Support, and Informational Support, while the Dependent Variable is the Provision of DM Diet. Thirty-eight respondents were selected randomly from the total population using the N-1 formula. Data were collected using the Family Support questionnaire and analyzed using a correlation test with α = 5%. Results: Assessment support (42%), instrumental support (61%), and information support (55%) were reflected as family support and categorized as sufficient. Diet provision for diabetic patients is also considered sufficient (53%). However, the correlation test showed no significant relationship between family support and diet provision for diabetic patients (sig 0.462). Conclusions: Although family support was a sufficient criterion in this study, this support did not significantly affect the diet management of diabetic patients. This result indicates that other factors may influence the patient's diet more.